2021
DOI: 10.31234/osf.io/rx8jc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biological Essentialism Correlates with (But Doesn’t Cause?) Intergroup Bias

Abstract: People with biological essentialist beliefs about social groups also tend to endorse biased beliefs about individuals in those groups, including stereotypes, prejudices, and intensified emphasis on the group. These correlations could be due to biological essentialism causing bias, and some experimental studies support this causal direction. Given this prior work, we expected to find that biological essentialism would lead to increased bias compared to a control condition and set out to extend this prior work i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Chen & Ratliff, 2018), more positive attitudes toward other groups (e.g., gay people; Haslam & Levy, 2006), and less blame for moral wrongdoing (e.g., Bailey et al, 2021). These relationships can be quite complex, as highlighted in recent work by Bailey and Knobe (2023), Mandalaywala (2020), and Peretz-Lange (2021. But most relevant for our purposes, essentialism has been shown to shape language use and vice versa (e.g., Ritchie, 2021).…”
Section: Essentialism About Social Groups and Identitiesmentioning
confidence: 84%
“…Chen & Ratliff, 2018), more positive attitudes toward other groups (e.g., gay people; Haslam & Levy, 2006), and less blame for moral wrongdoing (e.g., Bailey et al, 2021). These relationships can be quite complex, as highlighted in recent work by Bailey and Knobe (2023), Mandalaywala (2020), and Peretz-Lange (2021. But most relevant for our purposes, essentialism has been shown to shape language use and vice versa (e.g., Ritchie, 2021).…”
Section: Essentialism About Social Groups and Identitiesmentioning
confidence: 84%
“…And indeed, Oldham and Kasser (1999) found that reading a vignette that focuses on the genetic and neuroendocrine causes of homosexuality, led to less homonegativity in students. Other studies, however, did not find this influence of etiological beliefs on homonegativity, and suggest that causality might go in the opposite direction (Bailey and Knobe 2021): People often seem to rationalize their pre-existing attitudes by endorsing certain statements about the nature and origin of homosexuality. Moreover, even if it would turn out that findings about the genetic or endocrine roots of homosexuality would be instrumental in combatting homonegativity, this reasoning could itself be branded as a subtle form of homonegativity.…”
Section: Kitcher’s Argument and Homosexualitymentioning
confidence: 91%
“…et al (2010), Yzerbyt, Corneille, andEstrada (2001), Pauker et al (2016), andGallagher andBodenhausen (2021) for findings that support a positive relationship between essentialism and stereotyping. See Ritchie and Knobe (2020) and Bailey and Knobe (2021) for alternative views. The latter study present evidence that (biological) essentialism is correlated, but doesn't cause, stereotyping and prejudice.…”
Section: Orcidmentioning
confidence: 99%